2021
DOI: 10.1038/s41598-021-88162-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the variation in potential evapotranspiration and surface wet conditions in the Hancang River Basin, China

Abstract: Evapotranspiration is an important component of the water cycle, and possible trends in evapotranspiration can, among others, influence water management and agricultural production. Potential evapotranspiration (ETp) is a measure of the ability of the atmosphere to remove water from the surface through the processes of evaporation and transpiration. It plays an important role in assessing regional dry–wet conditions and variations in meteorological conditions. This study analyzed the change trends of monthly E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…This may be that the study area is located in the subtropical monsoon region, and the east Asian summer circulation is enhanced during the early rice growth period, resulting in increased precipitation. ET can be regarded as one of the most important factors for indicating climate change at the catchment scale[55], and our research supports this view. Meanwhile, the interannual variation of ET is closely related with many ecological factors.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…This may be that the study area is located in the subtropical monsoon region, and the east Asian summer circulation is enhanced during the early rice growth period, resulting in increased precipitation. ET can be regarded as one of the most important factors for indicating climate change at the catchment scale[55], and our research supports this view. Meanwhile, the interannual variation of ET is closely related with many ecological factors.…”
supporting
confidence: 85%
“…The results of this study have a slightly higher error than that in the previous study. The bias of the SEBAL model's estimation of ET is mainly due to the following factors: (1) The SEBAL model relies on instantaneous surface temperature, and the selection of hot and cold pixels in the imagery is subjective, which has a great impact on the accuracy of ET estimation; (2) The SEBAL model has been proven to be applicable for estimating ET in flat surfaces with relative accuracy, while it tends to have a high bias when applied to mountainous areas [54], which may lead to some increase in bias due to the presence of some hilly areas in our study area; and (3) Studies have shown that even a thin layer of clouds can lead to large errors when calculating sensible heat fluxes [55].…”
Section: Estimation Accuracy Of the Sebal Model For Daily Et In The G...mentioning
confidence: 99%
“…The dataset was generated by utilizing dynamic annual 300 m Landcover data and downscaled ECMWF ERA5-Land hourly data. Our ET dataset and operational model have a wide range of potential applications, including monitoring historical and current water use changes at the eld scale worldwide 59 , improving estimates of groundwater use and feeding into water balance, assessing food production and risks associated with droughts 12 and other shocks like con icts, monitoring the availability of water resources in river basins 13 , and supporting climate-smart agriculture strategies, such as smart irrigation scheduling 59 . The ET trend analysis across land cover types and climatic regions has revealed complex and intricate spatial patterns, with both increasing and decreasing trends in ET.…”
Section: Discussionmentioning
confidence: 99%
“…The two types of evapotranspiration are often considered for practical purposes of water resource management like guiding crop irrigation (Allen et al, 1998;Wen et al, 2016). ET p is an indispensable input variable for many land surface models and hydrologic models to compute ET a and other water budget components (Chen and Dudhia, 2001;Ala-aho et al, 2017), and plays a significant role in assessing regional dry and wet conditions and variations in meteorological conditions (Vicente-Serrano et al, 2010;Beguería et al, 2014;Yang et al, 2019;Zhang and Wang, 2021;Zhou et al, 2021). Therefore, quantification of ET p determines the performance of such models regarding the water flows, mixing and balance to better understand the interactions between climate and hydrology.…”
Section: Introductionmentioning
confidence: 99%